Refuge of the honored : social organization in a Japanese retirement community - Kinoshita, Yasuhito, 1953- (University of California Press, 1992)
Faced with the decline of the traditional family and the explosive growth of the over-65 population, the Japanese are looking for new ways to care for their elders. This study documents the birth of a major social phenomenon in Japan - the planned retirement community.